Idiopathic Portal Hypertension: A Rare Cause of Recurrent Hematemesis Melena - Griskalia Christine; Irsan Hasan (The Indonesian Society for Digestive Endoscopy, 2011)
Idiopathic portal hypertension (IPH) known as non-cirrhotic portal fibrosis (NCPF) is a constellation of liver disorders, in which liver cirrhosis is not present and the main clinical and pathological findings are encountered in the portal venous system. Patients usually come to hospital with esophageal varices and upper gastrointestinal bleeding; however, it is often misdiagnosed as liver cirrhosis. Its etiology is still unknown, but some evidences and epidemiological studies suggest that it is a multifactorial disease with genetic basis. The laboratory evaluation in IPH reveals only mild and subtle abnormalities predominantly related to hypersplenism. The major complications of IPH are esophageal varices and hypersplenism. Endoscopic sclerotherapy or band ligation, shunt surgery, and transjugular intrahepatic portosystemic shunt (TIPS) are modalities to treat the complications of IPH. The case report reported about diagnosis and treatment of a 20-year-old male with idiopathic portal hypertension. Keywords: idiopathic portal hypertension, non-cirrhotic portal fibrosis, diagnosis, treatment